Eco-Critical Language Awareness for ELT Pre-Service Teachers: Practicing the Concept Into Practice - Hasanul Misbah (CV. Creative Tugu Pena, 2024)
Eco-Critical Language Awareness (Eco-CLA), as a powerful concept to bring about environmental justice, produces eco-friendly humans with the relevant literature and language instruction. This article provides the practice of Eco-CLA in English Language Teaching (ELT) classroom by not only focusing big scheme of degraded environment condition and its worrying future impact on earth in short and long period. However, it draws the process of how ELT pre-service teachers are introduced to the ecological issues, reflect their identity and initiate pedagogical implication in ELT instructions. This research conducted a case study that involved 9 participants separated in 7 classes that were selected through the purposive sampling technique. The result of research scopes: (1) the students report on their relevant eco-literature; (2) the missing environmental values from their cultures and the drawbacks for the current surrounding situation and; (3) the momentarily appropriate responses (pedagogical implication) for the reformulation of those values to take a part into real actions in the future.